PENGARUH STRUKTUR AKTIVA, PROFITABILITAS, DAN KEBIJAKAN DIVIDEN TERHADAP STRUKTUR PENDANAAN PADA INDUSTRI PERBANKAN YANG TERCATAT DI BURSA EFEK INDONESIA - Arnida Wahyuni (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
Companies in choosing the funding structure is filled with the financing needs of its own capital (equity) or filled with foreign capital (debt) must consider a variety of factors. Asset structure, profitability, and dividend policy are several factors that affect the decision making structure of the financing company. The purpose of this study was to determine and analyze the influence of the structure of assets, profitability, and dividend policy on the funding structure of the banking industry are listed on the Indonesia Stock Exchange. The study was conducted on 22 samples of banking companies listed in Indonesia Stock Exchange using time series data from 2008 to 2012 and cross section called the pooling of data. The variables used are the structure of assets, profitability, and dividend policy as independent variables and the dependent variable funding structure. This study uses linear regression and multiple regression analysis to see the contribution of each variable individually and simultaneously to affect the structure of the funding is used to finance the operations of the company. The results show that the structure of assets has a more significant effect on the funding structure of the banking industry than profitability and dividend policy. This means that the asset structure is a better yardstick in assessing the company funding decisions based on this research. The test results also showed that the structure of assets, profitability, and dividend policy simultaneously influence on the structure of the banking industry funding.